An Interesting Case of Ingrowing Hair - Huang J; Yang Q; Lv P; Xiong X; Liu O (Dove Medical Press, 2023)
Jiangxia Huang,1 Qianru Yang,1 Pan Lv,1 Xiaoyan Xiong,2 Ougen Liu1 1Department of Dermatology, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People's Republic of China; 2Department of Ophthalmology, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People's Republic of ChinaCorrespondence: Ougen Liu, Department of Dermatology, The Second Affiliated Hospital of Nanchang University, 1 Minde Road, Nanchang, Jiangxi, 330006, People's Republic of China, Email 13576296646@163.comAbstract: Cutaneous pili migrans is a rare condition caused by embedded hair shafts or fragments which presents as a mobile black linear rash and is easily confused with cutaneous larva migrans. "Ingrowing hair", in which the hair shaft grows inside the skin and burrows into the uppermost dermis rather than exiting the skin, is much rarer, and only 8 cases have been reported thus far, all in Asian men. We report a case of a 22-year-old Chinese male with a 4 cm-long black linear rash that migrated from the anterior abdomen to the left lower abdomen. The black lines represented hair shafts with follicular structures. The lesion disappeared immediately after hair removal. No recurrence occurred in 4 weeks of follow-up. To our knowledge, this is the first description of ingrowing hair occurring in the abdomen.Keywords: cutaneous pili migrans, ingrowing hair, creeping hair